Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan(Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Subiyantari, Kiki; , Basworo Dibyo, S.E, M.Si (2017)
ABSTRACT This research aims to know the influence of good corporate governance financial performance against company: (study on the manufacturing companies listed on the Indonesia stock exchange by 2013-2015). This type of research is a type of quantitative research population in this research is the manufacturing companies listed on the Indonesia stock exchange (idx) of the 2013-2015. The sample in this research is the manufacturing company listed in BEI who published reports finance from 2013-2015, and the company has the full data sample related research data analyst in this study by using multiple linear regression analysis. The results showed the size of the Board of the independent Commissioners have no effect significantly to ROA demonstrated value of sig 0634 > 0.05. Disclosure effect significantly to the ROA is indicated by the value of the sig 0000 < 0.05. Simultaneously the size of Board of Commissioners are independent and disclosure influence on ROA of 0.001 < 0.05 Keywords: the size of the Board of Commissioners are independent, disclosure, ROA